Simulation Study of AlN Spacer Layer Thickness on AlGaN/GaN HEMT - Shrestha, Niraj Man; Wang, Yuen Yee; Li, Yiming; Chang, E. Y. (Himalayan Physics, 2013)
High electron mobility transistor (HEMT)Two-dimensional electron gas (2DEG) formed at AlGaN/GaN interface is a critical part to tune the characteristic of AlGaN/GaN HEMT devices. Introduction of AlN spacer layer in between AlGaN and GaN layer is one of the way to improve 2DEG density, mobility, and drain current. Carrier concentration, mobility and conduction band offset for different spacer layer thickness was simulated by using Silvaco simulation tool. Our device simulations showed that carrier concentration, mobility are enhance on introduction of AlN spacer layer in HEMT. In addition, carrier properties of HEMT also depend on thickness of spacer layer. Our simulation showed that the mobility of 2DEG attains its maximum value at the 0.5 nm thick AlN layer but carrier concentration increases with spacer thickness. Finally, drain current increases with increasing spacer layer thickness and reach maximum value at 1.2nm thick spacer layer. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 14-17 Uploaded date: 12/22/2013